Sediment recycling at the slab-mantle interface andfore-arc metasomatism: experimental production ofK-rich metasomes - Gülmez, Fatma; Prelević, Dejan; Förster, Michael W.; Buhre, Stephan; Günther, Jennifer (Research Square Platform LLC, 2023)
Abstract Sediment contribution to the mantle is the key step for the generation of orogenic magmatism to produce its isotopic and geochemical inventory. Even though they are exceptional for the subduction settings, there are worldwide samples of arc-related ultrapotassic mafic magmas which require complex multi-stage processes along with sediment melting. To understand the metasomatism leading the mantle to produce ultrapotassic mafic melts we simulated the reactions of depleted (harzburgite)and fertile (lherzolite) mantle with subducted carbonate-rich sediment at relatively cold (800-850 oC) and shallow (2 GPa, 60-80 km) slab-mantle interfaces. The progressive devolatilization of the sediments can trigger the formation of immiscible and conjugate carbonatitic and silicic melts which flux the mantle to develop exotic minerals and dolomitic melts. The metasomatic growth product is a wehrlite composed of clinopyroxene, phlogopite, carbonate minerals, and amphibole